The Effects Of Risk Based Bank Rating On Stock Return During Covid-19 Of BUKU IV Banks In Indonesia - Daryanto, Wiwiek Mardawiyah; Meiliawati, Putri Tresna (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
On December 31, 2019, the Wuhan City Health Commission, China, announced a cluster of cases of pneumonia, which causes the disease Covid-19. Indonesia's Gross Domestic Product (GDP) began to weaken at the end of the first quarter of 2020 from 4.9% to 2.9% (Q-o-Q), and then declined sharply in the second quarter of around -5.32%. The next quarter still saw negative growth but with less severity. Due to the Covid-19 crisis, investors began to hesitate to invest and withdraw their funds from the stock market, causing the Indonesian stock exchange (IDX) in Q1-2020 to fall 29.83% (YoY). In addition, it also led to a decline in banking stock prices, where the INFOBANK15 index fell from Rp.1,033.43 in Q4-2019 to Rp.732.54 in Q1-2020, or decreased by 29.12%. This study aims to determine the level of soundness based on the Risk Based Rating (RBBR) and the effect of the health level of the bank on bank stock returns. This research uses purposive sampling technique. RBBR analysis is used to determine the soundness of each RBBR ratio and is obtained from secondary data on the quarterly financial statements of seven publicly audited banks in Q4-2018 to Q1-2021. Banks under BUKU IV are in a healthy and very healthy condition based on the RBBR method, and research shows that NPL, LDR, ROA have a significant and positive effect on stock returns. Meanwhile, NIM and CAR have no effect on stock returns.